Complex Neutrosophic Soft Matrices Framework: An Application in Signal Processing - Madad Khan; Saima Anis; Kainat Bibi; Sohail Iqbal; Florentin Smarandache (Journal of Mathematics)
In this paper, we introduce the concept of complex neutrosophic soft matrices. We define some basic operations including complement, union, and intersection on these matrices. We extend the concept of complex neutrosophic soft sets to complex neutrosophic soft matrices and prove related properties. Moreover, we develop an algorithm using complex neutrosophic soft matrices and apply it in signal processing.